Regulation of the inducible chloramphenicol acetyltransferase gene of the Staphylococcus aureus plasmid pUB112. - Brückner, R (1985)
Analyses of deletion mutants of the gene for chloramphenicol (Cm) acetyltransferase (CAT) carried by the staphylococcal plasmid pUB112 revealed a regulatory region, which is indispensable for Cm-inducible cat gene expression, located 70 bp in front of the CAT-coding sequence. This region consists of a possible ribosome binding site followed by an open reading frame coding for a peptide of nine amino acids and overlaps partially with an inverted repeat capable of forming a stem-loop structure. Deletion of the ribosome binding site and of parts of the open reading frame abolishes inducibility and results in a low-level cat gene expression, if the inverted repeat remains intact. Deletion of the 5' part of the possible stem leads to high-level constitutive CAT synthesis. The inverted repeat, therefore, exhibits negative control on cat gene expression whereas the preceding ribosome binding site is needed to enhance CAT synthesis in the presence of an inducer. These results suggest that translation of a leader peptide is a prerequisite for Cm-induced cat gene expression and that ribosome stalling on cat leader mRNA caused by Cm opens the stem-loop structure thereby releasing its negative effect on CAT synthesis.